Ocenka effektivnosti trenirovki v tjaželoatleticeskich vidach sporta s ucetom polimorfizmov gena miostatina - Aksenov, M.O. (Vestnik sportivnoj nauki; Sports science bulletin, 2018)
The article highlights the long-term research findings estimating weightlifting athletes training efficiency with regard to myostatin gene (MSTN) genotypes. A computer program to analyze and plan weightlifting training has been developed. Some highly skilled athletes were genotyped according to their MSTN gene; their volume of training load and their training efficiency were also figured out, together with the time span necessary to meet the "Master of Sports of Russia" standard. The data obtained were carefully analyzed and resulted in a Pedagogical experiment with participation of a control and experimental groups differing in their MSTN genes genotypes. The subjects having genotype LL MSTN proved higher effectiveness of power performance training. The findings of bioimpedance analysis of muscle mass amount and some other criteria have also confirmed a more effective training process across the experimental group in comparison to the control one. The conducted experiment has proved the analysis findings. Some practical recommendations on planning athletes` training with regard to their genotypes have been developed.